Proton exchange of carbonic acid and methylamine complex accelerated by a single-water molecule via intermolecular hydrogen bonding: A theoretical investigation - Pakuna Panbo; Apirak Payaka; Rusrina Salaeh; Rathawat Daengngern (My University, 2023)
A theoretical investigation of the microsolvation effect on proton exchange (PE) between carbonic acid and methylamine (CA-MTA) has been explored by quantum dynamics simulations. The structural, energy, and dynamic properties of the complexes with and without an explicit water molecule are elucidated at the molecular level. The reactions have been clarified into different types: single-step PE (SSPE) and stepwise PE (SWPE). Without the water molecule, the SSPE mechanism is hardly found but observable with a low probability of 0.2. In particular, the water molecule interacting through intermolecular hydrogen-bonded network between CA and MTA could affect PE in both SSPE and SWPE mechanisms. To our findings, the existing water molecule plays the significant role in shortening intermolecular hydrogen bonding interactions within the complex resulting in increasing the probability up to 0.92. Hence, one water molecule could provide reliable results to represent the significant activity that occurs for the proton exchangeability of the CA and MTA complex.
Keywords: Carbonic acid; Spectroscopy and Quantum Chemical Studies